2018
DOI: 10.1101/484808
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The role of African buffalo in the epidemiology of foot-and-mouth disease in sympatric cattle and buffalo populations in Kenya

Abstract: Transmission of pathogens at wildlife-livestock interfaces poses a substantial challenge to the control of infectious diseases, including for foot-and-mouth disease virus (FMDV) in African buffalo and cattle. The extent to which buffalo play a role in the epidemiology of this virus in livestock populations remains unresolved in East Africa. Here, we show that FMDV occurs at high seroprevalence (~77%) in Kenyan buffalo. In addition, we recovered 80 FMDV VP1 sequences from buffalo, all of which were sero… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
2
3
0
Order By: Relevance
“…The SAT1 strain nucleotide sequences are 88.3% to 94.5% identical to that of SAT1/TAN/22/2012 (GenBank accession number KM268899), and that of SAT2/KEN/K137/2014 is 92.3% identical to that of SAT2/TAN/5/2012 (KM268900) (7). The VP1 coding regions of the current viruses were identical to those of previously published VP1s for these samples (8). In the VP1 coding region, SAT1/KEN/K14/2014 and SAT1/KEN/K29/2014 had the highest identity (92.1% and 92.3%, respectively) to SAT1/K28/06 (HQ267529) (9).…”
Section: Announcementsupporting
confidence: 70%
“…The SAT1 strain nucleotide sequences are 88.3% to 94.5% identical to that of SAT1/TAN/22/2012 (GenBank accession number KM268899), and that of SAT2/KEN/K137/2014 is 92.3% identical to that of SAT2/TAN/5/2012 (KM268900) (7). The VP1 coding regions of the current viruses were identical to those of previously published VP1s for these samples (8). In the VP1 coding region, SAT1/KEN/K14/2014 and SAT1/KEN/K29/2014 had the highest identity (92.1% and 92.3%, respectively) to SAT1/K28/06 (HQ267529) (9).…”
Section: Announcementsupporting
confidence: 70%
“…Yet the slow spread of bTB from buffalo populations in southern KNP to those in the north between 1960–2005, and then among populations in Zimbabwe in 2009, may suggest limited indirect between‐group transmission of pathogens, despite the high levels of indirect contacts between groups that we observed. In accordance with this result, Omondi et al (2020) reported genetically distinct variants of FMD virus between neighboring groups of Cape buffalo in Kenya. How intergroup contacts affect pathogen dynamics may depend on other factors, such as population dynamics (e.g., density), geographic features (e.g., barriers), pathogen maintenance ability (e.g., through group size), and pathogen characteristics (e.g., infectiousness, incubation period, host diversity).…”
Section: Discussionsupporting
confidence: 59%
“…Additionally, three single-nucleotide deletions, two in the 5′UTR (sites 124 and 523) and one in the 3′UTR (sites 8144 to 8145), were present in A/KEN/K74/2016. The VP1 region was identical to the previously published VP1 sequence for this sample (GenBank accession number MH882567 [8]). Importantly, in the VP1 region, the identity to A/Zambia/90 was only 82.9%.…”
Section: Announcementmentioning
confidence: 65%